Hayek and the Red Tape: The Politics of Evaluation and Quality Assurance Reform – From Shortcut Governing to Policy Rerouting - Joakim Lindgren; Linda Rönnberg (Springer, 2022)
In this chapter, we draw attention to the important political dimension of the governing-evaluation-knowledge nexus. The aim is to describe and analyse the processes leading up to the two most recent national evaluation and quality assurance (EQA) systems in operation from 2011 to 2014 and from 2016 onwards by analysing the formation of the respective EQA systems and the actors involved in these processes. The chapter outlines political justifications and ideological beliefs and highlights central shifts and continuities in these processes. We explore how formation of EQA systems can be understood within a wider context of the work of governing by contrasting the fast, competitive “shortcut governing” from the 2011–2014 EQA system with the more dialogue- and consensus-oriented process implying a “policy rerouting” later, as manifested in the process leading up to the 2016 EQA system. We also discuss quality assurance expansion in the context of higher education policymaking.
The Governing-Evaluation-Knowledge Nexus : Swedish Higher Education as a Case